2019
DOI: 10.1302/2046-3758.810.bjr-2019-0129.r1
|View full text |Cite
|
Sign up to set email alerts
|

Less iatrogenic soft-tissue damage utilizing robotic-assisted total knee arthroplasty when compared with a manual approach

Abstract: Objectives The use of the haptically bounded saw blades in robotic-assisted total knee arthroplasty (RTKA) can potentially help to limit surrounding soft-tissue injuries. However, there are limited data characterizing these injuries for cruciate-retaining (CR) TKA with the use of this technique. The objective of this cadaver study was to compare the extent of soft-tissue damage sustained through a robotic-assisted, haptically guided TKA (RATKA) versus a manual TKA (MTKA) approach. Methods A total of 12 fresh-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 44 publications
1
48
1
Order By: Relevance
“…Since the implementation of robot-assisted TKA, several studies have shown an improvement in alignment and precision with robotics; however, this was not shown to have a measurable effect in the short-term period despite no outliers in alignment in the robotic group and a range of 19%-24% of outliers in the conventional group [ 30 , 32 , 33 ]. There are advances with robotic arm–assisted surgery that have demonstrated less soft-tissue damage with saw precision [ 47 ], and balancing sensors being available on these platforms may allow for more surgeon feedback. There is also a potential confounding factor that low-volume total knee surgeons may not have the skill with conventional instrumentation as a high-volume fellowship-trained surgeon, such that previous studies performed by high-volume fellowship-trained surgeons comparing short-term results may not reflect the entire population of surgeons as well as a large database may capture.…”
Section: Discussionmentioning
confidence: 99%
“…Since the implementation of robot-assisted TKA, several studies have shown an improvement in alignment and precision with robotics; however, this was not shown to have a measurable effect in the short-term period despite no outliers in alignment in the robotic group and a range of 19%-24% of outliers in the conventional group [ 30 , 32 , 33 ]. There are advances with robotic arm–assisted surgery that have demonstrated less soft-tissue damage with saw precision [ 47 ], and balancing sensors being available on these platforms may allow for more surgeon feedback. There is also a potential confounding factor that low-volume total knee surgeons may not have the skill with conventional instrumentation as a high-volume fellowship-trained surgeon, such that previous studies performed by high-volume fellowship-trained surgeons comparing short-term results may not reflect the entire population of surgeons as well as a large database may capture.…”
Section: Discussionmentioning
confidence: 99%
“…MAKO robotic arm–assisted surgery has demonstrated some advantages over conventional instrumentation, particularly in a reduction of soft tissue damage from the haptically bounded saw blade [ 18 ]. Early data have also demonstrated an improved accuracy of component placement and limb alignment compared with conventional techniques [ 19 ], although long-term data on survivorship have not yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…The cadaveric study from Hampp et al looking at soft tissue preservation in MTKA and hRATKA noted the stereotactic boundary constraint on the sawblade may help prevent soft tissue damage [4]. While many other robotic systems use cutting blocks or similar methods, new TKA robotic system applications that are haptic-based-such as the application used in Hampp et al [4]-help protect the PCL. Learning more about the effect of the PCL on knee kinematics highlights the advantages of using hRATKA to preserve physiological motion.…”
Section: Discussionmentioning
confidence: 99%
“…With computer assisted orthopaedic surgery, there are opportunities to preserve soft tissue in total knee arthroplasty (TKA). Hampp et al compared the soft tissue damage between manual total knee arthroplasty (MTKA) and haptic-based robotic-arm assisted total knee arthroplasty (hRATKA) in a cadaveric study and found that the hRATKA specimens had significantly less damage than the MTKA specimens [4]. This was particularly true for the posterior cruciate ligament (PCL) [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation